Efektivitas dan Efisiensi Visualisasi Data Laporan Keuangan Terhadap Keputusan Investasi: Studi kasus pada mahasiswa S1 Akuntansi Universitas Bengkulu - Ahmad Ikhsan Fikri; Danang Adi putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The right investment decision in an entity is important for every potential investor in order to get the right and profitable investment. This study aims to determine whether data visualization is able to influence investment decisions in an entity. This research uses secondary data sources in the form of company financial statements which are then visualized. The object of this research is a S1 Accounting student of Bengkulu University. The results showed that the effectiveness and efficiency of data visualization had a positive effect on investment decisions in S1 Accounting students of Bengkulu University.